Classification in theory and practice - Batley, Sue (Oxford : Chandos Publishing, 2014)
Following on from the first edition of this book, the second edition fills the gap between more complex theoretical texts and those books with a purely practical approach. The book looks at major library classification schemes in use in Europe, UK and the USA, and includes practical exercises to demonstrate their application. Importantly, classifying electronic resources is also discussed. Classification in Theory and Practice aims to demystify a very complex subject, and to provide a sound theoretical underpinning, together with practical advice and development of practical skills. Chapters.
Classification schemes for specialist collectionsClassifying digital resources; The future of classification; End note; References; Answers to practical exercises; Dewey Decimal Classification -- DDC 23; Library of Congress Classification; Universal Decimal Classification abridged edition; Classification scheme for a photographic library; Index.
Previous edition: 2005.
Print version record.
Includes bibliographical references at the end of each chapters and index.
Keywords: Classification; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Classification; Electronic books